Mutations in Spliceosomal Genes PPIL1 and PRP17 Cause Neurodegenerative Pontocerebellar Hypoplasia with Microcephaly. - Chai, Guoliang; Webb, Alice; Li, Chen; Antaki, Danny; Lee, Sangmoon; Breuss, Martin W; Lang, Nhi; Stanley, Valentina; Anzenberg, Paula; Yang, Xiaoxu; Marshall, Trevor; Gaffney, Patrick; et al. (Neuron, 2021)
Autosomal-recessive cerebellar hypoplasia and ataxia constitute a group of heterogeneous brain disorders caused by disruption of several fundamental cellular processes. Here, we identified 10 families showing a neurodegenerative condition involving pontocerebellar hypoplasia with microcephaly (PCHM). Patients harbored biallelic mutations in genes encoding the spliceosome components Peptidyl-Prolyl Isomerase Like-1 (PPIL1) or Pre-RNA Processing-17 (PRP17). Mouse knockouts of either gene were lethal in early embryogenesis, whereas PPIL1 patient mutation knockin mice showed neuron-specific apoptosis. Loss of either protein affected splicing integrity, predominantly affecting short and high GC-content introns and genes involved in brain disorders. PPIL1 and PRP17 form an active isomerase-substrate interaction, but we found that isomerase activity is not critical for function. Thus, we establish disrupted splicing integrity and "major spliceosome-opathies" as a new mechanism underlying PCHM and neurodegeneration and uncover a non-enzymatic function of a spliceosomal proline isomerase.
Keywords: Amino Acid Sequence; Animals; Cell Cycle Proteins; Cerebellar Diseases; Cohort Studies; Female; Gene Knockout Techniques; HEK293 Cells; Heredodegenerative Disorders, Nervous System; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microcephaly; Mutation; Pedigree; Peptidylprolyl Isomerase; Protein Structure, Secondary; Protein Structure, Tertiary; RNA Splicing Factors; Spliceosomes